Classical Heritage. Roman Sculpture in the Middle Ages: the Case of Two Twisted Columns in the Church of St. Charles Borromeo in Cave - Forti, Barbara (Actual Problems of Theory and History of Art, 2015)
In the church of the convent of St. Charles Borromeo in Cave (Rome), two twisted columns, dating back to the late 11th or early 12th century (on a comparative basis), are kept. The two columns, similar to another couple in the Church of Trinità dei Monti in Rome, represent a particularly fortunate case, since the model is recognizable and still surviving: in fact, they look reduced size replicas of the monumental columnae vitineae, likely produced in the Eastern part of the Empire no later than the 3rd century AD and reused in the now dismembered Constantinian pergola in the ancient Vatican basilica. The origin and function of the columns in Cave are unknown. Anyway, both their propensity for figurative art and the relief style can be useful elements to relate with other contemporary artworks. This group of artifacts allows us to redefine a varied scenery of Roman art between the 11th and the 12th century, where, besides the most famous “non-iconic” tendency — systematically practiced since the early 12th century by the marmorarii conventionally defined as “Cosmati” — the presence of a “figurative” current should be noticed.